Examining the impact of psychosocial safety climate on working conditions, well-being and safety of healthcare providers: a scoping review - Mustapha Amoadu; Dorcas Frempomaa Agyare; Patience Fakornam Doe; Susanna Aba Abraham (BMC Health Services Research)
Abstract Background In contemporary healthcare systems, the well-being and safety of healthcare providers are pivotal for sustaining a resilient healthcare system. The concept of Psychosocial Safety Climate (PSC) emerges as a crucial framework influencing job design and employee perceptions in organisational settings, although its application within healthcare settings remains relatively underexplored. The aim of this review was to explore the buffering effect of PSC and its impact on working conditions, well-being and performance. Method This scoping review followed Arksey and O’Malley’s recommendations and PRISMA-ScR reporting checklist. Databases, including PubMed, Scopus, Central, JSTOR, and additional online sources such as Google Scholar were searched. Only peer-reviewed studies published in English that have measured PSC using PSC-12 or PSC-4 were included in this study. Findings High PSC environments correlated with enriched job resources, fostering resilience, positive job performance, and reduced job demands. Conversely, low PSC settings were linked to increased job demands, compromised well-being, and adverse job performance outcomes. Notably, PSC acted as a buffer, mitigating the negative impacts of high job demands on well-being and reinforcing positive associations between job resources, support, and performance facets among healthcare professionals. Conclusion This review highlights the pivotal role of PSC in shaping the work environment, well-being, and performance of healthcare providers. Prioritising PSC within healthcare settings is crucial to safeguarding the well-being of healthcare providers and improving patient outcomes. Future research should further explore the relationships between PSC, burnout, and other influencing factors, employing diverse methodologies to capture its comprehensive impact within healthcare settings.